Information Theft Crime - Bentareef, Mohamed Abdulmohsin; Abbadi, faycel Salah; Alfadly, Hiba Abdulmotalib (Journal of Legal Studies and Researches, 2022)
This study aims to identify the nature of the crime of information theft and the extent to which the traditional texts in Jordanian legislation apply to it, in addition to identifying the most important characteristics of the crime of information theft and the extent of the applicability of the act of embezzlement to information money after identifying the extent to which the description of money applies to information and software computer.